Differences in treatment goals and perception of symptom burden between patients with myeloproliferative neoplasms (MPNs) and hematologists/oncologists in the United States: Findings from the MPN Landmark survey. Issue 3 (30th September 2016) - Mesa, Ruben A.; Miller, Carole B.; Thyne, Maureen; Mangan, James; Goldberger, Sara; Fazal, Salman; Ma, Xiaomei; Wilson, Wendy; Paranagama, Dilan C.; Dubinski, David G.; Naim, Ahmad; Parasuraman, Shreekant; et al.
Abstract : BACKGROUND: This analysis of the myeloproliferative neoplasm (MPN) Landmark survey evaluated gaps between patient perceptions of their disease management and physician self‐reported practices. METHODS: The survey included 813 patient respondents who had MPNs (myelofibrosis [MF], polycythemia vera [PV], or essential thrombocythemia [ET]) and 457 hematologist/oncologist respondents who treated patients with these conditions. RESULTS: Greater proportions of physician respondents reported using prognostic risk classifications (MF, 83%; PV, 59%; ET, 77%) compared with patient recollections (MF, 54%; PV, 17%; ET, 31%). Most physician respondents reported that their typical symptom assessments included asking patients about the most important symptoms or a full list of symptoms, whereas many patient respondents reported less specific assessments (eg, they were asked how they were feeling). Many patient respondents did not recognize common symptoms as MPN‐related. For example, approximately one‐half or more did not believe difficulty sleeping resulted from their MPN (MF, 49%; PV, 64%; ET, 76%). Physician respondents underestimated the proportion of patients who had symptomatic PV or ET at diagnosis compared with patient respondents. There was discordance regarding treatment goals: among patient respondents with MF or PV, "slow/delay progression of condition" was the most important treatment goal, whereas physician respondents reported "symptom improvement" and "prevention of vascular/thrombotic events, " respectively. Finally, more than one‐third of patient respondents were not "very satisfied" with their physician's overall management/communication. CONCLUSIONS: The care and satisfaction of patients with MPN may be improved with increased patient education and improved patient‐physician communication. Cancer 2017;123:449–458. © 2016 The Authors. Cancer published by Wiley Periodicals, Inc. on behalf of American Cancer Society . Abstract : This analysis of data from the myeloproliferative neoplasm (MPN) Landmark survey identified important gaps in patient and physician respondent perceptions about MPNs. Discordance in patient and physician respondent perceptions was observed in MPN‐related prognostic risk assessment, symptom burden, treatment goals and expectations, and treatment satisfaction.